Thailand Monthly Economic Monitor : August 23, 2022 - World Bank (Washington, DC, 2022)
The economic recovery continued to pick up in Q2 2022, expanding by 2.5 percent (yoy), due to a stronger-than-expected boost in private consumption and tourism, which offset weak goods exports. However, among the major ASEAN economies, Thailand’s recovery has proven to be the slowest and inflation the highest. To tame cost-push inflation, the Bank of Thailand recently began raising rates; however, monetary policy normalization is expected to be gradual as the recovery is not yet complete. The fiscal deficit remained large as the government continued to introduce measures to counter the impact of the rising cost of living and the pandemic. The rising cost of energy subsidies administered by the State Oil Fund may potentially add to public debt levels. The Thai baht strengthened due to expectations of a swifter economic recovery and the decline of the US dollar.